Removal of ceftriaxone and ciprofloxacin antibiotics from aqueous solutions using graphene oxide derived from corn cob - . Rinawati; A. Rahmawati; D.R. Muthia; M.D. Imelda; F.H. Latief; S. Mohamad; A.A. Kiswandono (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Preliminary studies on the exploration of carbonaceous materials from agricultural waste and their use as adsorbents for antibiotic removal have shown the potential to address a new threat to human health due to antibiotic residue. Therefore, this study developed and synthesized graphene oxide from corn cob for its efficiency in removing ceftriaxone and ciprofloxacin.METHODS: The Hummers methods were used to synthesize graphene oxide from corn cobs. Graphene oxide was characterized using Fourier transform infrared, scanning electron microscope-energy dispersive x-ray, and x-ray diffraction instruments. During the synthesis process, antibiotic adsorption tests were extensively conducted by exploring four variables, namely dosage of adsorbent, potential hydrogen, concentration, and contact time.FINDINGS: The result showed that graphene oxide from corn cob effectively removed 47 percent of ceftriaxone and 92.62 percent of ciprofloxacin. Furthermore, to ensure optimum use of the adsorbents, antibiotics ceftriaxone and ciprofloxacin weighing 40 milligrams and 20 milligrams. This is in addition to the initial concentrations of 14 and 2 parts per million, the potential of hydrogen 4, and contact times of 50 and 40 minutes, respectively.CONCLUSION: In conclusion, adsorbents made from corn cobs are better at the removal of ciprofloxacin from water than the antibiotic ceftriaxone. The difference in molecular structure affected the percentage of antibiotic adsorption onto graphene oxide derived from corn cob. This study underscores the potential of the derived material as a promising adsorbent for efficiently removing ciprofloxacin from aquatic environments. The use of agricultural waste as advanced materials to address antibiotic residue pollution provided additional environmental pollution.